Long-Term Caragana korshinskii Restoration Enhances SOC Stability but Reduces Sequestration Efficiency over 40 Years in Degraded Loess Soils - Zhijing Xue; Shuangying Wang; Anqi Wang; Shengwei Huang; Tingting Qu; Qin Chen; Xiaoyun Li; Rui Wang; Zhengyao Liu; Zhibao Dong (Atmosphere)
Caragana korshinskii, a key species in China’s Grain for Green Project on the Loess Plateau, is effective in enhancing soil C sequestration. However, whether its contribution to SOC (soil organic carbon) stability persists over multi-decadal restoration chronosequences remains unclear. Using the time–space substitution method, we investigated the SOC fractions (POC, particulate organic C, and MAOC, mineral-associated organic C) dynamics across soil depths (0–10, 10–30, and 30–60 cm) in a 40-year chronosequence of C. korshinskii restoration, which is located in a comprehensive managed watershed on the Loess Plateau, China. The results showed that the C. korshinskii restoration chronosequence improved soil C sequestration at different scales compared to abandoned sites. In the middle phase (10–30 years), the concentration of SOC peaked at 35.88 g/kg, exceeding natural grassland (32.33 g/kg). Above- and belowground biomass accumulation drove SOC enhancement. POC as transient C inputs, and MAOC through mineral interactions, reach a peak at 7.98 g/kg which shows the greatest increase (276.81%). In the subsequent phase (after 30 years), MAOC dominated SOC stabilization, yet SOC fractions declined overall. MAOC contribution to SOC stability plateaued at 20–30%, constrained by soil desiccation from prolonged root water uptake. C. korshinskii provides the optimal SOC benefits within 10–30 years of restoration, highlighting a trade-off between vegetation-driven C inputs and hydrological limits in arid ecosystems. Beyond 30 years, C. korshinskii’s high water demand reduced SOC sequestration efficiency, risking the reversal of carbon gains despite initial MAOC advantages.